Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Manufaktur Dalam Perspektif Teori Agensi: (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2018-2020) - Aulia Fatiha Kurniadi; Dwi Urip Wardoyo (CV. Ulil Albab Corp, 2022)
This research was conducted with the aim of knowing the effect of company characteristics, namely company size, profitability, company profile, number of commissioners and leverage on the disclosure of corporate social responsibility. The sample used in this study uses 50 manufacturing companies listed on the IDX from 2018 to 2020 with information on social responsibility disclosures and a summary of financial data obtained through the annual reports of manufacturing companies. The technique used in conducting this research is purposive sampling method and data management is carried out using multiple linear regression analysis. The final result of this study will show that firm size, firm profitability, and the number of commissioners have an effect on the disclosure of corporate social responsibility in the perspective of agency theory.